2021
DOI: 10.1093/biolre/ioab144
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and proteome dynamics of cervical remodeling in the mouse during pregnancy

Abstract: During gestation, the female reproductive tract must maintain pregnancy while concurrently preparing for parturition. Here, we explore the transitions in gene expression and protein turnover (fractional synthesis rates [FSR]) by which the cervix implements a transition from rigid to compliant. Shifts in gene transcription to achieve immune tolerance and alter epithelial cell programs begin in early pregnancy. Subsequently, in mid-to-late pregnancy transcriptional programs emerge that promote structural reorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Previous bulk transcriptomic and proteomic studies suggest a marked change in epithelial cell phenotype and function during early cervical softening relative to NP (Nallasamy et al, 2021). To define the epithelial subtypes and cell state transitions induced in the early softening period, we compared epithelial subtypes in NP and GD6.…”
Section: Resultsmentioning
confidence: 94%
“…Previous bulk transcriptomic and proteomic studies suggest a marked change in epithelial cell phenotype and function during early cervical softening relative to NP (Nallasamy et al, 2021). To define the epithelial subtypes and cell state transitions induced in the early softening period, we compared epithelial subtypes in NP and GD6.…”
Section: Resultsmentioning
confidence: 94%
“…The POP landscape reveals four main biological processes that operate in epithelial cells, fibroblasts, and the surrounding ECM of the female urogenital tract: EMT, immune response activation, ECM modulation, and fibroblast survival and apoptosis. During pregnancy and (vaginal) delivery, similar changes in immune response activation and ECM modulation than in the POP landscape occur [ 20 , 21 ], which is interesting as increased parity and vaginal delivery are established environmental risk factors for developing POP [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic changes in ECM proteins, mainly collagen, decorin, elastin, glycosaminoglycans, and hyaluronic acid, occur in cervical remodeling in labor ( 302 , 321 324 ). Proteomic studies have shown that highly cross-linked collagens were replaced by newer, less cross-linked collagen during parturition ( 324 ), resulting in increased tissue compliance in cervical ripening. Aside from collagen, hyaluronic acid is essential due to its role as a component of the ECM.…”
Section: Preterm Birth As a Disease Of The Maternal Tissues And Organsmentioning
confidence: 99%